OPTIMIZATION OF STONE GRINDING PRODUCTS WITH FUZZY MULTY-OBJECTIVE LINEAR PROGRAMMING (FMOLP) APPROACH AT CV. ABC - Dyfebri, Rizal (Journal Knowledge Industrial Engineering (JKIE), 2023)
Mining is an industry or company that processes natural resources, where the production process is carried out in various ways, both manually and with material processing machines. The results of the production supply produced by the company always meet the needs (Demand) needed in each region. From the results of observations, there is an opportunity to be able to produce more and more profitable production capacity so that it is necessary to optimize the production results that have been recorded using the Fuzzy Multi-Objective Linear Programming approach method processed with LINGO software. So that there is hope that the results of the data processing will produce maximum values, limit values ​​or target values ​​from a production process that have met the requirements according to the supply and demand data from the mining. Namely, 72 tons of Urug Sand, 80 tons of fine sand, 64 tons of gravel.